Single-phase single-stage high DC voltage multiplier converter - Muhammad, K.S.; Omar, A.M.; Mekhilef, Saad (2005)
This paper proposed a single-phase single-stage high DC voltage Multiplier converter. The convertion of high DC voltage converter without a DC-link is involved. A high frequency transformer using ETD 59 ferrite core with ratio 1:1 is used as energy storage and also providing isolation. Cockcroft-Walton circuit is connected at secondary side of the transformer. AC input is controlled by IGBT switch which the current flow in both directions of the transformer to fully utilize the transformer core. The current flow is controlled by the IGBTs using PWM technique. Experimental and simulation results are provided to show the effectives of the proposed technique.